2019
DOI: 10.1002/jaal.947
|View full text |Cite
|
Sign up to set email alerts
|

Going Global With Project‐Based Inquiry: Cosmopolitan Literacies in Practice

Abstract: As our world becomes increasingly interconnected, complex global challenges necessitate cross‐cultural collaborative efforts. Thus, developing cosmopolitan literacies among students and teachers becomes ever more important. Believing that cosmopolitan literacies are central to being literate in contemporary times, the authors build on their existing project‐based inquiry model to include global themes (e.g., poverty, global water and sanitation, climate change) and cross‐cultural exchange. This theory‐into‐pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…According to Heitin (2016), Spires and Bartlett, for example, suggested that “Web 2.0 tools are social, participatory, collaborative, easy to use, and are facilitative in creating online communities” (p. 2; see also Spires & Bartlett, 2012). More recently, Spires, Himes, Paul, and Kerkhoff (2019) extended their understanding of digital literacy practices as ways of sharing to encompass the cosmopolitan literacies useful for digital, cross‐cultural exchanges around global themes such as poverty and climate change. Still other scholars in the Education Week (“Special Report,” 2016) spotlight have described digital communication practices more aptly with terms such as digital coding , digital citizenship , and digital storytelling .…”
Section: What Is Digital Literacy?mentioning
confidence: 99%
“…According to Heitin (2016), Spires and Bartlett, for example, suggested that “Web 2.0 tools are social, participatory, collaborative, easy to use, and are facilitative in creating online communities” (p. 2; see also Spires & Bartlett, 2012). More recently, Spires, Himes, Paul, and Kerkhoff (2019) extended their understanding of digital literacy practices as ways of sharing to encompass the cosmopolitan literacies useful for digital, cross‐cultural exchanges around global themes such as poverty and climate change. Still other scholars in the Education Week (“Special Report,” 2016) spotlight have described digital communication practices more aptly with terms such as digital coding , digital citizenship , and digital storytelling .…”
Section: What Is Digital Literacy?mentioning
confidence: 99%
“…As literacy educators continue to grapple with how best to prepare youth to make the most of digital literacies for global meaning making, we see opportunities for more international classroom exchanges and connectedness. Fostering cosmopolitanism through globally oriented education initiatives such as Space2Cre8 (Hull & Stornaiuolo, 2010) and Project‐Based Inquiry Global (Spires, Himes, Paul, & Kerkhoff, 2019) offers inspiration for collaborations that strengthen global connectedness. The Global Read Aloud initiative also provides a platform that connects readers around the world in common literacy endeavors.…”
Section: Inviting a Global Turnmentioning
confidence: 99%
“…In addition to responding to the larger call for literacy research and practice toward global citizenship (Beach, 2017;Morrell, 2017;Tierney, 2017), this study advances PBI Global research (Spires et al, 2018(Spires et al, , 2019 through a full qualitative account using collective case study with students to examine critical inquiry and social action. This study focuses on a critical inquiry and social action project with students from one U.S. school to more closely examine the evolution of students' critical global perspectives throughout the course of the project.…”
Section: Social Actionmentioning
confidence: 99%
“…PBI Global developed from the researchers' work connecting disciplinary literacy to inquiry-based learning (Spires et al, 2016(Spires et al, , 2020; the framework has also been adapted for inquiry-based learning in a global context (Spires et al, 2018(Spires et al, , 2019. To explicitly connect the global themes addressed in each project to an internationally recognized agenda, PBI Global's focus on the 17 political, economic, environmental, and social issues targeted by UN member states for improvement by 2030 in the Sustainable Development Goals (SDGs; UN, n.d.).…”
mentioning
confidence: 99%